Suramin increases cartilage proteoglycan accumulation in vitro and protects against joint damage triggered by papain injection in mouse knees in vivo. Issue 2 (30th November 2017) - Guns, Laura-An; Monteagudo, Silvia; Kvasnytsia, Maryna; Kerckhofs, Greet; Vandooren, Jennifer; Opdenakker, Ghislain; Lories, Rik J; Cailotto, Frederic
Abstract : Objectives: Suramin is an old drug used for the treatment of African sleeping sickness. We investigated therapeutic repositioning of suramin to protect against cartilage damage, as suramin may interact with tissue inhibitor of metalloproteinase-3 (TIMP3). Methods: In vitro extracellular matrix (ECM) accumulation and turnover in the presence or absence of suramin were studied in the ATDC5 micromass model of chondrogenesis and in pellet cultures of human articular chondrocytes from osteoarthritis and control patients, by gene expression, protein analysis, colorimetric staining, immunoprecipitation, fluorimetric analysis and immunohistochemistry. To study suramin in vivo, the drug was injected intra-articularly in the papain model of joint damage. Disease severity was analysed by histology, immunohistochemistry and contrast-enhanced nanofocus CT. Results: In ATDC5 micromasses, suramin increased TIMP3 levels and decreased the activity of matrix metalloproteinases (MMPs) and aggrecanases. Suramin treatment resulted in increased glycosaminoglycans. This effect on the ECM was blocked by an anti-TIMP3 antibody. Direct interaction between suramin and endogenous TIMP3 was demonstrated in immunoprecipitates. Mice treated intra-articularly with suramin injections showed reduced cartilage damage compared with controls, with increased TIMP3 and decreased MMP and aggrecanase activity. Translational validation in human chondrocytes confirmed increased TIMP3 function and reduced cartilage breakdown after suramin treatment. Conclusion: Suramin prevented loss of articular cartilage in a mouse model of cartilage damage. The effects appear to be mediated by a functional increase of TIMP3 and a subsequent decrease in the activity of catabolic enzymes. Thus, suramin repositioning could be considered to prevent progressive cartilage damage and avoid evolution toward osteoarthritis.